Historical Monuments In Surkhandarya Region (Eurasian Journal of Humanities and Social Sciences, 2024)
The historical, cultural, and spiritual heritage of each state plays an important role in its development, leading the people to a new stage of spiritual growth. The role of ancient, scientific, religious, and artistic heritage in the formation of national spirituality is of great importance. This heritage, both tangible and intangible, is a great treasure left over from our ancestors, and today the Uzbek people pay special attention to its in-depth study and respectful treatment of cultural monuments that are considered the heritage of our ancestors.